2018
DOI: 10.13189/ujer.2018.060402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Activities Done by Using Activity Based Posters on the Students' Academic Achievements, Retention Levels in Their Learning

Abstract: The aim of the study is to investigate whether the activity based posters have an effect of on the ninth class students' academic achievements and the retention levels in their learning. The research was carried out with 60 students at one of the state schools in The Central Anatolia Region of Turkey in 2015-2016 academic year. Study-"Celebrities" unit teaching-took 6 weeks in both experimental group and control group. This study was conducted according to the "pre-test-post-test control group model" which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Based on the findings, it was concluded that activity-based instruction increased students' interest in social studies course and enabled effective learning. It has been determined that this result is similar to other studies (Ebret, 2015;Coşkun and Eker, 2018;Gülsoy, 2020;Seçgin, 2020) concluding that activity-based teaching increases students' interest, motivation and attitudes towards the lesson. As a result, in the activity-based teaching process, the students were active throughout the process and accordingly the following results were reached; a) contribute to concept learning, b) realize meaningful learning, c) students can use their knowledge to create a brand-new product, d) increase their interest in social studies course, e) realize effective learning.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on the findings, it was concluded that activity-based instruction increased students' interest in social studies course and enabled effective learning. It has been determined that this result is similar to other studies (Ebret, 2015;Coşkun and Eker, 2018;Gülsoy, 2020;Seçgin, 2020) concluding that activity-based teaching increases students' interest, motivation and attitudes towards the lesson. As a result, in the activity-based teaching process, the students were active throughout the process and accordingly the following results were reached; a) contribute to concept learning, b) realize meaningful learning, c) students can use their knowledge to create a brand-new product, d) increase their interest in social studies course, e) realize effective learning.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…However, there are some studies on poster activities with similar qualities. When the results of the studies in which the students created their own posters were examined, it was seen that the results of those studies were similar to the results of this research, such as contributing to meaningful learning, ensuring active participation, increasing interest and motivation towards the lesson, increasing academic success and finally contributing to the development of creative thinking (Chaveznava, Yousuf and Caldeslast, 2006;Coşkun and Eker, 2018;Yıldız, 2021).In the last part of the study, students were asked to evaluate the activitybased teaching process. With this evaluation, it was tried to determine how the activities affected the individual learning of the students.…”
Section: Conclusion and Discussionsupporting
confidence: 54%
“…Childrens character values can develop, for instance gratitude and give thanks, praise one another, empathy, conflict resolution, honesty, discipline, responsibility. Social education posters are very necessary because they can help children and parents find out information, messages and ideas (Christenbery, & Latham, 2013;Coskun, I& Eker, 2018). Other finding was also concluded that after using poster media, give positive impact, especially for cognitive development on early childhood 4-5 years old (Indriyani, 2018).…”
Section: Figure 1 Social Education Poster About Negative Body Imagementioning
confidence: 99%
“…Posters have many benefits in the educational context. They are colorful, attractive learning media (Coşkun & Eker, 2018) which cater for different learning styles (El-Sakran & Prescott, 2015) and which create a more stimulating and interesting class environment (Prichard & Ferreira, 2014). Moreover, they allow for creativity (Abdul Aziz & Jusoff, 2009), individuality (D'Angelo, 2011), originality (Cook & Fenn, 2013), and independent thought (D'Angelo, 2010).…”
Section: Traditional Postersmentioning
confidence: 99%